THE ROLE OF ADVANCED COMPUTER TECHNOLOGIES AND ARTIFICIAL INTELLIGENCE IN SURGERY - Atakhanov Sanzharbek Anvarovich; Sharipov Ruzali Murrdali ogli (Bright Mind Publishing, 2025)
This article examines the role of advanced computer technologies and artificial intelligence (AI) in modern surgery. Key areas of digital integration are analyzed, including robotic surgery, computed tomography and 3D visualization, navigation systems, machine learning for diagnostics and prediction, and clinical decision support systems. The advantages — precision, reduced invasiveness, shorter intervention and rehabilitation time — as well as the risks — technical failures, accountability, ethical, and legal issues — are evaluated. Practical examples of AI applications in preoperative preparation, surgical planning, and interactive navigation are provided, along with prospects such as big data integration, personalized surgery, autonomous robots, and the combination of AI with bioengineering. Emphasis is placed on the need for a multidisciplinary approach, protocol standardization, quality control, and the importance of training surgeons to use digital tools.
Keywords: surgery, artificial intelligence, robotic surgery, navigation systems, 3D visualization, machine learning, digital medicine, safety.